An Overview on Anti-Chronic Myelogenous Leukaemia Efficacy of Spergulin-A (International Journal of Innovative Research in Computer Science & Technology, 2022)
One of the main causes of mortality in the  21st century has been cancer. Even among cancer, chronic  myelogenous leukaemia (CML) is one of the main causes for cancer associated death. Despite its ubiquity the  breadth of therapy is restricted by its high cost and lack of  effectiveness. Spergulin –A, a saponin which is a  triterpenoid, isolated from an n-butanol fraction of the  flowering plant Glinus oppositifolius has been reported  previously for its anti-leishmanial activity. In this study,  Spergulin-A was isolated from Glinus oppositifolius and  its Identification and structural confirmation was achieved  by NMR, after which it was tested for its anti-CML action.  As per the present results, Spergulin-A was found to cause  growth inhibition and trigger apoptosis in K562, a cell line  of chronic myelogenous leukaemia, origin. Moreover,  Spergulin-A has demonstrated no detrimental effects  against normal cell lines. Based on these results, it can be  reasonably concluded that Spergulin-A may be used as an  anti-CML agent.
Keywords: Apoptosis; Chronic Myelogenous Leukaemia; Reactive Oxygen Species (ROS); Spergulin A